History of Kedungcangkring Batik as Local Wisdom of Sidoarjo Regency 1940-2024: Sejarah Batik Kedungcangkring sebagai Kearifan Lokal Kabupaten Sidoarjo Tahun 1940-2024 - Sidiq, Firmansyah Salsabila; Fitriany, Aulia; Mubarok, M. Khusni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The research aimed to examine and explore more deeply how the development of Kedungcangkring Batik as a form of local wisdom in Sidoarjo Regency. In addition, the batik business that has been running from time to time since 1940 to 2024 is the subject of discussion in the research. The role of Batik Kedungcangkring and its relevance to the world of education, especially history education is also the purpose of the research. This research is classified as qualitative research using the historical approach method with four stages, namely heuristics, source criticism, interpretation, and historiography. The research also combines literature review and field research. The results show that Kedungcangkring batik business developed into a business that is able to adapt through various times through a combination of strategies such as product diversification, motif and color innovation, utilization of digital technology, empowerment of local communities and collaboration with the government and external parties. Batik Kedungcangkring also contributes to the world of education as a source of local history, raising awareness of history and cultural identity, becoming an interactive learning medium, and strengthening local-based entrepreneurship education. Various challenges and opportunities in maintaining the business also color the dynamics of the development of Batik Kedungcangkring Sidoarjo. In addition, Batik Kedungcangkring not only focuses on the development of its business but also develops the socio-cultural aspects of the surrounding community through batik training and school construction.